Una gramática escolar interlingüística. Hacia una enseñanza reflexiva de las lenguas en contextos multilingües - Rodríguez-Gonzalo, Carmen (Huarte de San Juan. Filología y Didáctica de la Lengua, 2022)
The challenge of multilingual education requires the teaching of curricular languages, which promotes reflection on the use and transfer of language to develop students’ communicative competence. In this line of thinking, the Egramint project proposes the development of an interlinguistic school grammar as an instrument of teacher training and intervention in the classroom. Methodologically, it is a qualitative-ethnographic investigation in three phases. In the first phase, on which this article focus, we address the documentary analysis of the official curricula of the Spanish scope to delimit how school grammar is configured in them. The results show the predominance of identification over the manipulation or reflective use, as well as the links of the grammatical reflection with the comprehension and elaboration of texts, in aspects such as planning and revision. Interlinguistic treatment is also advocated, especially in territories with two first languages.
Keywords: teacher training, curricula, reflection on the language, metalinguistic competence, interlinguistic school grammar